2017
DOI: 10.1007/s00216-017-0625-y
|View full text |Cite
|
Sign up to set email alerts
|

Droplet volume variability as a critical factor for accuracy of absolute quantification using droplet digital PCR

Abstract: Accurate and precise nucleic-acid quantification is crucial for clinical and diagnostic decisions, as overestimation or underestimation can lead to misguided treatment of a disease or incorrect labelling of the products. Digital PCR is one of the best tools for absolute nucleic-acid copy-number determination. However, digital PCR needs to be well characterised in terms of accuracy and sources of uncertainty. With droplet digital PCR, discrepancies between the droplet volume assigned by the manufacturer and mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
64
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 25 publications
4
64
0
Order By: Relevance
“…Discrepancies between partition volumes assigned by the manufacturer and measured in independent laboratories have been reported for ddPCR platforms [38, 58, 8082]. At NIB, Bio-Rad’s QX100/QX200 platform has been tested most rigorously.…”
Section: Digital Pcr For Absolute Quantification Of Copy Number and Tmentioning
confidence: 99%
See 4 more Smart Citations
“…Discrepancies between partition volumes assigned by the manufacturer and measured in independent laboratories have been reported for ddPCR platforms [38, 58, 8082]. At NIB, Bio-Rad’s QX100/QX200 platform has been tested most rigorously.…”
Section: Digital Pcr For Absolute Quantification Of Copy Number and Tmentioning
confidence: 99%
“…With a new line of cartridges, the software was updated to consider a volume of 0.85 nL. Nevertheless, measurement of the new cartridges showed a deviation from Bio-Rad’s default value, with volumes of 0.767 nL [81] and 0.715 nL [82]. The most recent study [82] not only showed that the volume of droplets is significantly lower but also that the volume of droplets is affected by type of super mix (for probes or EvaGreen) and the type of droplet generator (manual or automated).…”
Section: Digital Pcr For Absolute Quantification Of Copy Number and Tmentioning
confidence: 99%
See 3 more Smart Citations